2019
DOI: 10.1001/jamacardio.2019.1870
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D Supplementation and Cardiovascular Disease Risks in More Than 83 000 Individuals in 21 Randomized Clinical Trials

Abstract: IMPORTANCE Observational studies have reported an association between low serum vitamin D levels and elevated risk of cardiovascular disease (CVD) events, but such studies cannot prove causation because of possible unmeasured confounding.OBJECTIVE We conducted a meta-analysis of randomized clinical trials that tested the association of vitamin D supplementation with reduced CVD events and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
2
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(210 citation statements)
references
References 46 publications
(149 reference statements)
6
173
2
5
Order By: Relevance
“…In general, the results in this field are conflicting. A comprehensive 2019 meta-analysis by Barbarawi et al [95] including 83,000 participants did not find beneficial cardiovascular outcomes following vitamin D supplementation. However, further studies are needed to clarify if special subgroups could benefit from this intervention.…”
Section: Discussionmentioning
confidence: 95%
“…In general, the results in this field are conflicting. A comprehensive 2019 meta-analysis by Barbarawi et al [95] including 83,000 participants did not find beneficial cardiovascular outcomes following vitamin D supplementation. However, further studies are needed to clarify if special subgroups could benefit from this intervention.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a study to assess the long-term effect of supplementation of vitamin D in ischemic stroke patients with low vitamin D levels found a significant improvement in the outcome after three months [168]. Nevertheless, the value of vitamin D supplementation in preventing stroke is still unclear, as a recent meta-analysis of randomized clinical trials conducted in more than 80,000 patients found no clinical benefit of vitamin D supplementation in reducing the incidence of (as opposed to outcome from) major cardiovascular events, including stroke and cardiovascular death [169]. Therefore, it is possible that vitamin D supplementation is less effective for preventing cardiovascular events than for limiting post-stroke injury and improving outcome.…”
Section: Vitamin D Deficiency and Strokementioning
confidence: 99%
“…Whereas the cardiovascular safety of vitamin D supplementation is well established (7), the safety of calcium supplementation has been challenged over the last decades following publication of observational studies reporting increased incidence of various cardiovascular (CVD) endpoints including coronary artery disease (CAD) or coronary heart disease (CHD; which develops when the coronary arteries become too narrow), among users. This safety issue continues to be a scientific controversy, with several meta-analyses of studies with diverging outcomes having been published (8,9).…”
Section: Editorialmentioning
confidence: 99%